AN M/M/1/N QUEUE WITH WORKING BREAKDOWNS AND VACATIONS-AN APPROACH TO COST ANALYSIS. Issue 1 (May 2021) - Deepa, B.; Kalidass, K.; Vijayalakshmi, V.
Abstract: In this paper, we consider an M/M/1/N queue with working breakdown and two types of server vacations. Sensitivity analysis of the model is performed to aissue with the point of streamlining service rates by limiting the normal expense per unit time using the direct search method.